Analysis and visualization of digital advertising data using EDA on payment point online bank applications - Putra, Wisnu Buana; Ayu, Kurnia Gusti (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This research explores the effectiveness of digital advertising within Payment Point Online Bank (PPOB) applications using Exploratory Data Analysis (EDA) and data visualization techniques. With the rapid growth of internet users and online transactions in Indonesia, businesses face challenges in optimizing digital marketing strategies. By analyzing data from various digital ad campaigns, the study develops a comprehensive advertising dashboard to enhance decision-making and report generation. Key metrics such as cost, impressions, clicks, app installs, registrations, and purchases are examined to assess campaign performance. The dataset comprises advertising data, which includes campaign data (Region, Network, Device) and demographic data (Age and Gender) stored in spreadsheets. The total campaign dataset contains 20,151 rows, while the demographic dataset comprises 125 rows, collected from March to May 2023. Findings indicate that the majority of users (90%) access the application through mobile phones, while 10% utilize tablets. Regarding cost-effectiveness, the UAC_AppInstall campaign demonstrates the lowest Cost per App Install (CPI) at 3141 Rupiah, while the UAC_AppRegistration campaign has the most efficient Cost per Registration (CPR) at 8892 Rupiah and the UAC_AppRetention campaign boasts the most efficient Cost per Purchase (CPP) at 235 Rupiah. Moreover, regional analysis shows that areas like West Java, Jakarta, East Java, and Central Java have the highest acquisition rates, while the eastern regions of Indonesia face challenges due to lower internet accessibility and digital literacy. The study provides valuable insights for marketing teams to optimize their strategies, enhance targeting approaches, and improve the overall effectiveness of digital advertising campaigns.